Analisis penerapan pelayanan kesehatan peduli remaja - Ida Arnita Ritonga; Tri Niswati Utami; Tengku Moriza (Jurnal Kesmas Prima Indonesia, 2022)
The Youth Care Health Program is a model of health services aimed at and accessible to adolescents, This study aims to analyze the implementation of the Youth Care Health Program in the Gunung Tua Community Health Center. This research design used analytical survey with cross sectional study design. The sample in this study were some of the teenagers in the work area of the Gunung Tua health center as many as 108 teenagers using purposive sampling technique. Data collection was carried out using a questionnaire. Data were analyzed using chi-square statistics and logistic regression. The results showed that there was an effect of providing adolescent information (p = 0,000), there was an effect of supporting examinations (p = 0,000). there was an effect of of counseling (p = 0,000), there was an effect of skills education (p = 0,000), there was an effect of referral on the implementation of the Youth Care Health Program in the work area of the Gunung Tua Community Health Center (p = 0,000). The conclusion in this study is that the variables of providing adolescent information, supporting examinations, counseling, education, skills, peer counselor training have an effect on the implementation of the Adolescent Care Health Program in the work area of the Gunung Tua Community Health Center, while the most influential variable is the counseling variable (p = 0.022). . Suggestions in this study are that there is a need for broader socialization of the implementation of the PKPR program to adolescents through socialization to schools, cadets, giving pamphlets or leaflets containing information about the existence of PKPR which provides special services for adolescents.